Importance of Tourism in the Economic Development of Uzbekistan - Tursinbaevich, Adilchaev Rustem (Indonesian Journal Publisher, 2024)
This study explores the role of tourism in the economic development of Uzbekistan. It discusses the different types of tourism, reforms in the sector, and the potential impact of tourism on raising the morale of the people. The study aims to provide insights into the tourism industry's contribution to the national economy and its importance for cultural and economic development.